Implementation And Design of Security System On Motorcycle Vehicles Using Raspberry Pi3-Based GPS Tracker And Facedetection - Sari, Indah Purnama; Al-Khowarizmi, Al-Khowarizmi; MD, Pipit Putri Hariani; Perdana, Adidtya; Manurung, Asrar Aspia (Sinkron : jurnal dan penelitian teknik informatika, 2023)
One of the nations where land transportation is frequently employed is Indonesia, particularly on motorbikes or two-wheeled vehicles. Since there is not much economic growth to maintain the high level of sales, there are many people without jobs, which leads to criminality, particularly motorcycle theft. The rate of motorbike theft in society is currently rising. The researchers developed a security system using a GPS Tracker whose control was handled by a two-channel relay in response to the rise in motorbike theft. The webcam camera produces the greatest images when it is hidden by a tree. 100% of the time, Relay Components work to control the horn and electricity. Due to the short read-time of the location the first time, GPS has a high accuracy. The Raspberry Pi3 can send, receive, and process commands to the motorcycle security system. The motion sensors, vibration sensors, raspberry pi microcontrollers, relays, and servo motors make up the system architecture in general. This method operates when the motor produces a lot of vibration. The sensor will relay the vibration to the Raspberry Pi microcontroller's output and the microcontroller will then deliver a warning notification message. In the event of a theft, the motorcycle will be immediately within the owner's control. In addition, with security using facedetection, the public can detect the perpetrators of theft and it takes quite a long time to work on it. The security system on motorbikes using facedetection takes a long time to produce, but it can't be done optimally. The purpose of this creation is to improve the security system on motorcycles to make it more efficient and effective in identifying the perpetrators of theft. This system consists of a Raspberry Pi3 as the control center, a picamera as a face detector, and a buzzer as an alarm.